2013
DOI: 10.1200/jco.2013.31.15_suppl.6024
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of everolimus and sorafenib for the treatment of metastatic thyroid cancer.

Abstract: 6024 Background: Everolimus is an oral inhibitor of the mammalian target of rapamycin (mTOR). Unpublished work from the Fagin lab shows that mTORC1 is also required for the growth promoting effects of the oncoproteins RET/PTC, RAS and BRAF in rat thyroid PCCL3 cells. Further work shows synergy of mTORC inhibitors with RET kinase inhibitors in medullary thyroid cancer cell lines. Sorafenib is an oral kinase inhibitor with in vitro activity against multiple targets, including RAF, RET, VEGFR1, and VEGFR2 that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…The systematic review uncovered four relevant sorafenib trials that evaluated its use in RAI-R DTC patients in combination with another targeted agent (see Table 3 ) such as tipifarnib (Hong et al, 14 Cabanillas et al 15 ), temsirolimus (Sherman et al 29 ), and everolimus (Sherman et al 30 ). Tipifarnib is a farnesyl transferase inhibitor, while temsirolimus is an intravenous inhibitor of mTOR and everolimus is an mTOR inhibitor given by mouth.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review uncovered four relevant sorafenib trials that evaluated its use in RAI-R DTC patients in combination with another targeted agent (see Table 3 ) such as tipifarnib (Hong et al, 14 Cabanillas et al 15 ), temsirolimus (Sherman et al 29 ), and everolimus (Sherman et al 30 ). Tipifarnib is a farnesyl transferase inhibitor, while temsirolimus is an intravenous inhibitor of mTOR and everolimus is an mTOR inhibitor given by mouth.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of sorafenib and everolimus shows promising results: partial response rates were higher than those reported for sorafenib as a single agent, with a partial response of 56% for non-medullary TC. However, several grade-4 adverse events occurred possibly related to the drug ( 158 ).…”
Section: Implications For Therapymentioning
confidence: 99%
“…More recently, the same authors evaluated 38 patients with thyroid cancer (ten MTC and 28 DTC) and showed that the combination of sorafenib and everolimus, another mTOR inhibitor, achieves better clinical responses than for sorafenib alone: PR 55% and SD 37%. 79 Brose et al 80 enrolled 35 patients with evidence of progression by RECIST criteria on sorafenib treatment and demonstrated an additional median PFS of 13.7 months, a SD ≥6 months of 54%, and a PR of 3% adding everolimus to sorafenib. 80 …”
Section: Efficacy Studies Of Sorafenib In Patients With Thyroid Cancementioning
confidence: 99%